Quantitative predictions of cavitation presence and erosion-prone locations in a high-pressure cavitation test rig - Koukouvinis, Foivos (Phoevos); Mitroglou, Nicholas; Gavaises, Manolis; Lorenzi, Massimo; Santini, Maurizio (My University, 2017)
Experiments and numerical simulations of cavitating flow inside a single-orifice nozzle are presented. The orifice is part of a closed flow circuit, with diesel fuel as the working fluid, designed to replicate the main flow pattern observed in high-pressure diesel injector nozzles. The focus of the present investigation is on cavitation structures appearing inside the orifice, their interaction with turbulence and the induced material erosion. Experimental investigations include high-speed shadowgraphy visualization, X-ray micro-computed tomography (micro-CT) of time-averaged volumetric cavitation distribution inside the orifice as well as pressure and flow rate measurements. The highly transient flow features that are taking place, such as cavity shedding, collapse and vortex cavitation (also known as 'string cavitation'), have become evident from high-speed images. Additionally, micro-CT enabled the reconstruction of the orifice surface, which provided locations of cavitation erosion sites developed after sufficient operation time. The measurements are used to validate the presented numerical model, which is based on the numerical solution of the Navier-Stokes equation, taking into account compressibility of both the liquid and liquid-vapour mixture. Phase change is accounted for with a newly developed mass transfer rate model, capable of accurately predicting the collapse of vaporous structures. Turbulence is modelled using detached eddy simulation and unsteady features such as cavitating vortices and cavity shedding are observed and discussed. The numerical results show agreement within validation uncertainty with the obtained measurements.